Alterations in bile acid synthesis in carriers of hepatocyte nuclear factor 1α mutations. (6th May 2013) - Ekholm, E.; Nilsson, R.; Groop, L.; Pramfalk, C.
Abstract Objectives Heterozygous mutations in hepatocyte nuclear factor 1α (HNF1α) cause maturity onset diabetes of the young 3 (MODY3), an autosomal dominant form of diabetes. Deficiency of HNF1α in mice results in diabetes, hypercholesterolaemia and increased bile acid (BA) and cholesterol synthesis. Little is known about alterations in lipid metabolism in patients with MODY3. The aim of this study was to investigate whether patients with MODY3 have altered cholesterol and BA synthesis and intestinal cholesterol absorption. A secondary aim was to investigate the effects of HNF1α mutations on the transcriptional regulation of BA metabolism. Methods Plasma biomarkers of BA and cholesterol synthesis and intestinal cholesterol absorption were measured in patients with MODY3 (n = 19) and in matched healthy control subjects (n = 15). Cotransfection experiments were performed with several promoters involved in BA metabolism along with expression vectors carrying the mutations found in these patients. Results Plasma analysis showed higher levels of BA synthesis in patients with MODY3. No differences were observed in cholesterol synthesis or intestinal cholesterol absorption. Cotransfection experiments showed that one of the mutations (P379A) increased the induction of the cholesterol 7α‐hydroxylase promoter compared with HNF1α, without further differences in other studied promoters. By contrast, the other four mutations (L107I, T260M, P291fsinsC and R131Q) reduced the induction of the farnesoid X receptor (FXR) promoter, which was followed by reduced repression of the small heterodimer partner promoter. In addition, these mutations also reduced the induction of the apical sodium‐dependent bile salt transporter promoter. Conclusions BA synthesis is increased in patients with MODY3 compared with control subjects. Mutations in HNF1α affect promoters involved in BA metabolism.